Voices for Healthy Kids: a multisectoral collaboration to accelerate policy changes that promote healthy weight for all children and adolescents in the United States - Callahan,, Emily A (BMJ, 2018)
Emily Callahan and colleagues report how a multisectoral collaboration of more than 140 stakeholder organisations is advancing policy changes to improve food and physical environments in the United States to promote healthy weight for all children and adolescents